Characteristics and factors associated with adverse cutaneous drug reactions caused by traditional, complementary and conventional medicine in Malaysia - Nor Hazlin T,; Leelavathi Muthupalaniappen,; Zuhra Hamzah,; Adawiyah Jamil,; Dawn AA, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Traditional and Complimentary Medicines (TCMs) can potentially cause Adverse Cutaneous Drug Reactions (ACDRs). The aim of this study was to describe the characteristics of ACDRs due to TCMs and compare with those due to conventional medicine. This was a retrospective study with 134 cases being diagnosed with ACDR at the Dermatology Clinic of a tertiary hospital in Kuala Lumpur. Most (82.1%) ACDRs were caused by conventional drugs, while 17.9% were due to TCMs. Majority (70-75%) of the ACDRs were of mild to moderate severity. The most common ACDR to TCM was Exfoliative Dermatitis (ED) and Acute Generalized Exanthematous Pustulosis (AGEP) (both 16.7%) while maculopapular rash was the most common reaction for conventional medications (25.5%). The onset of adverse reaction to TCM was about 4 weeks (60.2%) while reactions due to conventional medication was earlier (1 to 6 days, 65.4%; p<0.05). The odds of developing delayed ACDR was 14 times more with TCM compared to conventional medicine (p<0.05). This study showed that ED and AGEP were the most common ACDR manifestations of TCM while macuplopapular rash was the most common manifestation of conventional medications. However, most of these reactions were of mild to moderate severity. ACDR due to TCM may manifest long after the initiation of these products and hence its use should be routinely inquired when patients present with skin problems. All suspected cases of ADRs to TCM should be reported to the Malaysian Adverse Drug Reactions Advisory Committee (MADRAC) for continuous pharmacovigilance of these products.